ANALISIS PENGARUH STRUKTUR MODAL, KEBIJAKAN DIVIDEN DAN EFISIENSI OPERASIONAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Niswah, Nasyiatu; Kurniawati, Lintang (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The purpose of this study is to examine how capital structure, dividend policy, and operational efficiency affect the financial performance of consumer products manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022. The annual financial accounts of selected businesses provided the data for this study through sampling techniques, resulting in 56 observations from 23 companies for three years. Multiple regression analysis is the method employed in this study. The findings indicated that overall, capital structure, dividend policy and operational efficiency impact financial performance in a major way. However, when the analysis is done separately, The only factor that significantly affects financial performance is capital structure; operational effectiveness and dividend policy have no discernible effects